The Requirements of Investing the Scientific Research in Achieving the Sustainable Development at Tabuk University from the Point of View of Faculty Members at the University - Alshehri, Haifa Abdulrhaman (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the requirements (administrative, financial, technical, and human) of investing the scientific research in achieving the sustainable development at Tabuk University, and the impact of variables: gender, scientific rank, published scientific production, and specialization in the sample responses. The descriptive survey approach, and the questionnaire consists of (42) phrases was used, and It was distributed to a sample of (141) faculty members. The results showed that the degree of importance of the requirements of investment in scientific research to achieve sustainable development in the University of Tabuk in general, came with a mean (2.48 out of 3) with a degree (high). All the axes came with a degree (high), where the axis arranged as follow: technical requirements, with a mean (2,50), administrative requirements, with a mean (2,49) human requirements, with a mean (2.47), and finally, the financial requirements, with a mean (2.44). The results also showed statistically significant differences (α ≤ 0.05) between the responses of the study sample according to gender, and for the benefit of females, and there were no statistically significant differences according to the variables of scientific rank, published scientific production and specialization, with the exception of the differences on the technical requirements, due to the published scientific production variable, for the benefit of who have (more than five research). Based on the results, the researcher recommended providing all the necessary requirements for investing in scientific research, and establishing a specialist to direct colleges to invest and develop research to serve development, in addition to proposals for future studies on the subject.
Keywords: Requirements; Scientific Research Investment; Sustainable Development; Tabuk University